My neighbor Totoro - Miyazaki, Hayao, 1941-; Dempsey, Rick; Hidaka, Noriko; Sakamoto, Chika; Itoi, Shigesato, 1948-; Fanning, Dakota; Fanning, Elle; Daly, Tim (Burbank, CA : Studio Ghibli, 2010)
Children discover a new world in a tree trunk inhabited by magical creatures called Totoros, which can't be seen by adults.
Originally released as a motion picture in 1988.
Features: World of Ghibli: an extraordinary interactive experience, Enter the lands: meet the characters and hear the story of the movie, Behind the studio: discover the film s inspiration through documentaries, including all-new interviews with Hayao Miyazaki, Storyboard presentation of the movie.
Japanese voices: Noriko Hidaka, Chika Sakamoto, Shigesato Itoi ; English voices: Dakota Fanning, Elle Fanning, Tim Daly, Pat Carroll, Lea Salonga, Frank Welker, Paul Butcher.
MPAA rating: G.
DVDs, Dolby digital 2.0 stereo.
In English or Japanese with optional French or Japanese subtitles.
Keywords: Animals, Mythical -- Juvenile films; Friendship -- Juvenile films; Video recordings for the hearing impaired; Children's films; Fiction films; Feature films; Animated films